2015
DOI: 10.1080/19359705.2015.1105115
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for HIV Pre-Exposure Prophylaxis (PrEP) Information Among Men Who Have Sex with Men (MSM) at Community Outreach Settings

Abstract: Community outreach efforts to increase HIV pre-exposure prophylaxis (PrEP) utilization by at risk men-who-have-sex-with-men (MSM) first need to elucidate preferences for learning about PrEP and linking to PrEP resources. In this pilot study, we observed that among MSM recruited through community outreach, HIV sexual risk-taking was significant, yet self-perceived PrEP knowledge was low and interest in learning more about PrEP was moderate. Most preferred learning about PrEP and being provided local PrEP clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…emergency departments) or non-healthcare settings (e.g. community-based organizations (CBOs)), minimum assessments may include knowledge of and eligibility for a range of risk-reduction strategies, including PrEP, in accordance with U.S. Centers for Disease Control and Prevention (CDC) recommendations, and healthcare provider and insurance status navigation needs [11]. For vulnerable individuals testing for HIV in healthcare settings, or having been referred for HIV prevention services by an acute care or non-healthcare testing site, possible assessments include the following: screenings for sexually transmitted infections, mental health disorders, substance abuse, intimate partner violence and trauma; adequacy of health insurance to cover necessary prevention services; and other primary or specialty care needs [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…emergency departments) or non-healthcare settings (e.g. community-based organizations (CBOs)), minimum assessments may include knowledge of and eligibility for a range of risk-reduction strategies, including PrEP, in accordance with U.S. Centers for Disease Control and Prevention (CDC) recommendations, and healthcare provider and insurance status navigation needs [11]. For vulnerable individuals testing for HIV in healthcare settings, or having been referred for HIV prevention services by an acute care or non-healthcare testing site, possible assessments include the following: screenings for sexually transmitted infections, mental health disorders, substance abuse, intimate partner violence and trauma; adequacy of health insurance to cover necessary prevention services; and other primary or specialty care needs [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…housing, employment, nutritional and social support) [12,13]. For individuals tested for HIV and having undergone basic risk assessments in acute and non-healthcare settings, linkage to culturally sensitive medical and other service providers with knowledge and experience providing or coordinating various primary HIV prevention interventions is essential [11]. These may include providers in primary care settings; reproductive, sexual, transgender or other community health programmes (including PrEP clinics); and intervention programmes at CBOs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies that have evaluated outreach strategies to increase PrEP uptake among high-risk individuals have resulted in fewer than 1% initiating PrEP (23). Thus, the optimal strategies for increasing PrEP uptake among individuals who may benefit from PrEP are not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…Age and education are the two other factors. In another pilot study of 209 participants without any intervention in the state of Rhode Island has shown that less than half of the HIV-negative people were willing to take PrEP in 2014, even though there was a high prevalence of condomless sex ( [8]). Knowledge of PrEP was low and interest in knowing more about PrEP through counseling and education was moderate, though electronic media and brochure was available.…”
Section: Prep In Msmmentioning
confidence: 99%
“…Since its approval in 2012, the low uptake of PrEP has been observed in the MSM community ( [8]). First of all, PrEP is only available in a few countries.…”
Section: Prep In Msmmentioning
confidence: 99%